Testes de vigor e viabilidade em sementes de niger (Guizotia abyssinica (L.f.) Cass.) - Gordin, Carla Regina Baptista (2015)
The biodiesel is used as a fuel with potential in the world and the niger (Guizotia abyssinica (L.f.) Cass.) stands out as a promising source. For the success of crop establishment is required the use of quality seeds and vigor tests are important in assessing the physiological potential of seeds, because complement the information obtained in the germination test. Thus, the aim of this work was adapt methodologies of vigor tests to evaluate the niger seeds physiological quality. Six lots of seeds were used, initially characterized as the water content; germination percentage, first count, germination speed index and mean germination time; emergence percentage, emergence speed index and mean emergence time on the field; initial stand and seedling length. The accelerated aging test was carried out by traditional and saturated salt solution (20, 40 g NaCl 100 ml-1) methods at temperatures of 41 and 45 °C for 24, 48, 72 and 96 hours. In controlled deterioration test the seeds had the water content adjusted to 16, 20 and 24% before being subjected to a temperature of 41 °C for 24 and 48 hours. In both experiments, after the deterioration period, the seeds were submitted to the germination test, accounting for the normal seedlings percentage. The cold test was performed procedures "with" and "without soil" in temperatures of 5, 10 and 15 °C for five days and was held the germination test. The seedling length test was performed on the substrates on paper and paper roll and in a greenhouse for 15 days, recording the total length and dry weight of 10 normal seedlings. In tetrazolium test, seeds were preconditioned on paper substrate at 25 °C for three hours and then immersed in a solution of 2,3,5-triphenyl tetrazolium chloride in concentrations of 0.075, 0.1 and 0.5% by 2, 4, 6, 8, 16 and 24 hours at 25 °C in the dark, and evaluated for viability after staining. The experimental design was completely randomized with four replications of 50 seeds. Data were subjected to variance analysis and means were compared by Tukey test (p <0.05). Based on the results, all of vigor tests used were efficient in physiological quality distinction of niger seeds, except the seedling length test and the seedlings dry mass evaluations. For the accelerated aging test recommended 20 g NaCl 100 ml-1 at 41 ° C for 24 hours method. The traditional method is not suitable for providing varying the water content between samples between the upper tolerable. For the controlled deterioration test recommends the use of seeds with 16% of water content for 24 hours. The cold test is indicated in temperature of 5 °C on paper. The tetrazolium test is promising for assessing the viability niger seed, recommending the use of 0.5% concentration of tetrazolium solution with for 24 hours.